2005
DOI: 10.1143/jjap.44.1923
|View full text |Cite
|
Sign up to set email alerts
|

Moisture-Resistive Properties of SiNx Films Prepared by Catalytic Chemical Vapor Deposition below 100°C for Flexible Organic Light-Emitting Diode Displays

Abstract: Silicon nitride (SiN x ) films were deposited on Si and polycarbonate (PC) substrates at temperatures below 100°C by a catalytic chemical vapor deposition (Cat-CVD) method. By adding H2 to source gases, SiH4 and NH3, it was possible to prevent the deterioration of film qualities in low-temperature deposition processes. H atoms produced from H2 are effective for increasing the film densities and improving passivation properties. The water vapor transmission rate of SiN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…An increase in T sub results in the enhancement of the migration of radical species, such as SiH 3 and NH 2 , and the desorption of H 2 gas on the surface of films. 23,24) We can observe the tendency to largely decrease the refractive indices in a long wavelength of 450-1000 nm by the DH stress for all three samples. The reduction in refractive index seems to increase for the films deposited at a low T sub of 100 °C.…”
Section: Optical Properties Of Sin X Films Under the Dh Testmentioning
confidence: 73%
“…An increase in T sub results in the enhancement of the migration of radical species, such as SiH 3 and NH 2 , and the desorption of H 2 gas on the surface of films. 23,24) We can observe the tendency to largely decrease the refractive indices in a long wavelength of 450-1000 nm by the DH stress for all three samples. The reduction in refractive index seems to increase for the films deposited at a low T sub of 100 °C.…”
Section: Optical Properties Of Sin X Films Under the Dh Testmentioning
confidence: 73%
“…For the cap layer, 150 nm-thick SiN x was deposited by PECVD at 200 • C. Finally, polymer film on array and SiN x layer were deposited. Noted that a SiN x cap layer under the polymer film on array stops the moisture permeation into the TGI [15,16], and prevents the hump phenomenon [17].…”
Section: Methodsmentioning
confidence: 99%
“…[3][4][5] We have so far demonstrated that silicon nitride (SiN x ) and silicon oxynitride (SiO x N y ) films deposited by Cat-CVD can be utilized as moisture barrier films. [6][7][8] In a conventional system for the deposition of SiN x films, silane (SiH 4 ) and ammonia (NH 3 ) are used as gas sources. The use of SiH 4 , however, is undesirable from the standpoint of safety because of its explosive nature, and the formation of moisture barrier films with a safer material is favorable.…”
Section: Introductionmentioning
confidence: 99%